INDONESIAN CHILDREN STORIES MULTIMEDIA APPLICATIONS USING MICROSOFT VISUAL BASIC 6.0 - Veronica Veronica; Dyah Ruri Irawati, SKom, MMSi Dyah Ruri Irawati, SKom, MMSi (Jurnal Sistem Informasi, 2005)
In this scientific writing explores the collection of folktales from several regions inIndonesia. With this application one can obtain information about these people'sstories come from several areas in Indonesia and made with attributes that do notmake it difficult for its users. This application can be executed on a computer that isrunning Windows-based operating system.